Effect of Self Help Group (SHG) to Stop Smoking Attitudes Among Students - Dianita Sugiyo; Fitri Asparati (Universitas Muhammadiyah Yogyakarta, 2016)
The smoking prevalence among youth aged more than 15 years old and so, raising 34,8 % of male and 2,7 % among those female one. Thus, health education program is needed in order to improve youth knowledge on the negative impacts of smoking. This study has been conducted among students of Mexhanical Engineering school in Uni- versitas Muhammadiyah Yogyakarta. This study was a quasy-experimen- tal study. The sample were 52 students who smoked and were divided into two groups, intervention and control gruop. The sampling tech- nique used was random sampling method. Test analysis used Wilcoxon test and Mann-Whitney for attitude. Results : The analysis test showed there was a significant effect of Self Help Group (SHG) on attitude with p=0,000 (0,05). There was a differences on knowledge between inter- vention and control groups with p=0,000 (p0,05). This new inven- tion on health education method using social media, is important to be developed. Facebook as one of the easy platform of social media to access, will giving more benefit to the community in achieving distance health education.